The Male-Child and the Principle of Reality in African Society: Educating the Male-Child away from the Grips of the Pleasure Principle towards the Reality Principle and Productivity through the Symbolic Order: A Transformative Perspective from Amu Djoleto in his ‘The Strange Man’ (Global Journal of Medical Research, 2023)
In two articles in the London Journal of Research and Social Sciences IJRISS 2019 2021 I explored sequentially the argument regarding the process of the formation of the human subject and how crucial it is for the individual s growth process to be moulded through integration into the symbolic order to enable human growth development and maturation mental stability the formation of identity and individuality and preparation for the need to labour The outcome of such growth and process is being able to focus on a stable object and being able to become productive and above all capable of promoting the development of sound mental health and civilization The subsequent article in 2021 explored the role of the mother in this formation process and the impact of women s writings on the same jeopardizing the formation of the human subject and the implications for mental health development and productivity especially for the male-child The effort was most relevant for the exploration of the creation of the human subject which is crucial especially on account of the need for the upbringing of male children to be able to negotiate their human existence away from the pleasure principle towards the reality principle in order to be capacitated towards grappling with the unknowns of life This article builds upon the same themes and arguments of the formation of the human subject through the symbolic order and the essential properties in the process of achieving a credible formation of the male individual through an exploration of how it can be achieved in spite of the challenges posed by unconscious drives in society to keep the male-child under the risk of death and eternal infantilism Amu Djoleto s novel The Strange Man demonstrates the process towards success of the male-child s upbringing to a certain extent within an African community It concludes that the role of the father in the formation of the human subject especially of the male-child can neither be taken for granted nor eliminated without dire consequences for its transition to the reality principle
Keywords: The male-child; human subject; identity; symbolic order; pleasure principle; reality principle; eternal infantilism; mental health